Gender in private and public spheres : expectations from Croatia's EU membership and the reality - Landripet, Ivan; Čulig, Benjamin; Kufrin, Krešimir (2008)
Introduction. "Attitude of Croatian citizens towards Croatia's membership in the European Union" was designed as a national study of attitudes, beliefs and awareness of Croatian citizens regarding the European Union, Croatia's accession to the EU and its membership in this supranational political and economic community. Special emphases within the study were put on potential effects of accession and membership related to legal and implementory harmonization with the EU standards in the area of human rights protection and particularly gender equality. The aim of the presentation, focused on the latter set of issues, is to provide a general account of the extent to which professional and family environments generate and perpetuate gender inequalities and stereotypes in Croatian society. Survey. The questionnaire that was administered consisted of 45 instruments and the total of 260 items (80 of which targeted gender-related issues). The field part of the survey was conducted by the method of face-to-face interviews in May of 2007 on a nationally representative sample of adult citizens (N=1005 ; general population). It was construed as a multistage probabilistic sample with the random selection of respondents within households, enabling generalizations on the target population with the maximal margin of error of ±3.1% (95% confidence level). Results. The assessed level of gender equality achieved in Croatia was examined with reference to traditional areas of discrimination against women. About three quarters of respondents expressed high level of criticism towards the current position of women in Croatia, agreeing that female citizens are more exposed to family violence, have a greater workload, are overrepresented in less-paid jobs, etc. The experience of various forms of gender/sex-based discrimination in the sphere of labor and employment is not particularly common, but the situation is much more unfavorable for women, who are several times as likely to be exposed to those forms of discrimination as men. Regarding the laws regulating social policy and labor market, Croatia will have to introduce a series of changes to harmonize them with EU's acquis communautaire. Most citizens tend to oppose changes they perceive as more likely to happen (for example, allowing women to work in harsh conditions and night shifts or leveling the age of retirement), whereas changes supported by the majority are perceived as less likely to take place (restrictions on overtime hours for mothers and fathers with young children or stimulations for fathers to take parental leaves). Such constellation of preferences and expectations represents an indirect, but undeniable basis for generating Europessimism. Finally, the private, family sphere appears to be a very significant locus of gender inequality. Although most citizens of both sexes declare sensitivity to different forms of discrimination against women and score relatively low on sexism, division of household chores between the spouses/partners in Croatian families is in close accordance with the stereotyped gender roles. Alongside with performing duties that are routine, time consuming and need to be executed on daily basis, women typically take on much greater workload. Childcare is also primarily a woman’s job: none of the activities related to it are performed more often by men. The perceived conflict between professional and family obligations does not seem striking, but among those that report it the percentage of women is twice as large. Same seems to be true when it comes to making concrete professional concessions due to raising children – women were forced to take up part-time jobs, sacrifice their carriers or even resign more often than men and are to a greater extent exposed to stress while attempting to reconciliate the two spheres.
ENG